EP229/#754 Long-term survival among patients with various histologic subtypes of advanced ovarian cancer enrolled in NCI clinical trials. (4th December 2022) - Jang, Allyson; Johnson, Caitlin; Mann, Amandeep; Somasegar, Sahana; Darcy, Kathleen; Tian, Chunqiao; Ueda, Stefanie; Kapp, Daniel; Chan, John K
Abstract : Objectives: To determine extended long-term survival of ovarian cancer patients after standard surgery and chemotherapy enrolled in NCI clinical trials Methods: Data on stage III epithelial ovarian cancer patients were obtained from three prospective randomized Gynecologic Oncology Group clinical trials (114, 158, 172). Chi-squared, multivariate Cox models, and log-rank tests were employed to determine overall survival. Results: Of 1, 526 patients enrolled, 75.7% had serous, 10.6% endometrioid, and 8.1% mixed epithelial, 3.3% clear cell, 2.3% mucinous histologies. Extended long-term OS (>15 years) was lowest in mucinous at 14.3% compared to clear cell (23.5%), serous (23.5%), mixed epithelial (25.8%), and endometrioid (34.2%) histologies (p<0.0001). On multivariate analysis, older age (>57 median age) (HR 1.23; 95%CI [1.09, 1.39]; p=0.0006), worse ECOG performance status (HR 1.42; 95%CI [1.14–1.77]; p=0.002), mucinous histology (HR 3.3; 95% CI [2.25, 4.86]; p<0.0001) predicted worse OS. On subanalysis of 35 patients with mucinous tumors, those who underwent intraperitoneal chemotherapy did not have an improved survival compared to intravenous therapy (p=0.22). Furthermore, those with low grade serous tumors had the highest long-term survival at 42.7% compared to only 20.9% in those with high-grade tumors (p<0.0001). Conclusions: Histology remains as an independent predictor for long term survival in ovarian cancer patients enrolled in clinical trials with central pathology review and after receiving standardized surgery and chemotherapy. Specifically, mucinous tumors demonstrated the worst survival of all histologies. Low grade serous had best prognosis after treatment.